« L’appel de la forêt » : une forêt primaire entre projet associatif et politique en faveur de la libre évolution - Alexandra Locquet (VertigO)
Since the 2000s, a series of initiatives have emerged in France and Europe to encourage the return of high-quality natural areas. These projects, which are mainly run by associations, aim to help tackle climate change and biodiversity loss. In France, projects encouraging ‘free evolution’ are mainly being developed around forest environments, although these practices are beginning to develop in other habitats. It is in this context that the Francis Hallé Association for Primary Forests (AFH) project emerged, with the ambition of restoring favourable conditions for the development of a 70,000 ha primary forest in a cross-border zone in Western Europe. This research, based on a research-action approach, examines how this sort of project promotes the emergence of new modes of action for protecting the environment, while at the same time politicising its subject. This paper explores the AFH project's position in the context of growing interest in free evolution strategies. It also explores both the strategy deployed by the organisation and the effects induced by the potential development of such an initiative in an area (use changes, economic activity reconfiguration, et cetera). The article shows that the studied initiative is complex and faces several limitations due to the ambition of its project, its association status and the absence of a precedent. AFH proposes a hybrid approach, being the meeting point and/or point of friction between institutional nature conservation practises and associative action. AFH's project, although not territorialized, contributes to promoting and putting forward for debate the free evolution principles as an approach to environmental management, a way of cohabiting with non-human beings and a means of socio-ecological transition.